(untitled) (Journal of the College of Basic Education, 2024)
Experience avoidance is the natural tendency of humans to avoid threatening or uncomfortable experiences, and this instinct can be attributed to their ability to adapt, from an evolutionary perspective taking practical steps towards reducing fear or anxiety means increasing the chances of survival and thus the spread of this behavioral response, and conversely, failure to respond to these emotions appropriately is likely to increase the chances of serious injury Adolescents certainly face problems related to the use of the Internet, mobile phones and video games, on the other hand, adolescents use these behaviors more than any other group, and feel that they are more knowledgeable about information and communication technology The current research aims to identify Experience avoidance among adolescents 1- 2-Significance of differences in experience avoidance according to gender variables (males – females( 3- Technology addiction among adolescents 4- Significance of differences in technology addiction according to gender variables (males – females) 5-The correlation between experience avoidance and technology addiction. To achieve the objectives of the research, the researcher intended to construct experience avoidance and its final form consists of (17) paragraphs. The researcher also built a technology addiction scale, and the scale in its final form consisted of (18) paragraphs. After verifying the psychometric properties, they were applied to the research sample consisting of (360). The results showed the following 1-The research sample members are characterized by a high level of avoiding the experience. 2-There are statistically significant differences between males and females in avoiding the experience, in favor of females. 3-The research sample members are characterized by a high level of technology addiction. 4-There are statistically significant differences between males and females in technology addiction, in favor of males. 5-There is a direct relationship between avoiding the experience and technology addiction. In light of the results achieved in the current research, the researcher came up with some recommendations and suggestions